Patient safety and estimation of renal function in patients prescribed new oral anticoagulants for stroke prevention in atrial fibrillation: a cross-sectional study. Issue 9 (27th September 2013) - MacCallum, Peter K; Mathur, Rohini; Hull, Sally A; Saja, Khalid; Green, Laura; Morris, Joan K; Ashman, Neil
Abstract : Objective: In clinical trials of dabigatran and rivaroxaban for stroke prevention in atrial fibrillation (AF), drug eligibility and dosing were determined using the Cockcroft-Gault equation to estimate creatine clearance as a measure of renal function. This cross-sectional study aimed to compare whether using estimated glomerular filtration rate (eGFR) by the widely available and widely used Modified Diet in Renal Disease (MDRD) equation would alter prescribing or dosing of the renally excreted new oral anticoagulants. Participants: Of 4712 patients with known AF within a general practitioner-registered population of 930 079 in east London, data were available enabling renal function to be calculated by both Cockcroft-Gault and MDRD methods in 4120 (87.4%). Results: Of 4120 patients, 2706 were <80 years and 1414 were ≥80 years of age. Among those ≥80 years, 14.9% were ineligible for dabigatran according to Cockcroft-Gault equation but would have been judged eligible applying MDRD method. For those <80 years, 0.8% would have been incorrectly judged eligible for dabigatran and 5.3% would have received too high a dose. For rivaroxaban, 0.3% would have been incorrectly judged eligible for treatment and 13.5% would have received too high a dose. Conclusions: Were the MDRD-derived eGFR to be used instead of Cockcroft-Gault in prescribing these new agents, many elderly patients with AF would either incorrectly become eligible for them or would receive too high a dose. Safety has not been established using the MDRD equation, a concern since the risk of major bleeding would be increased in patients with unsuspected renal impairment. Given the potentially widespread use of these agents, particularly in primary care, regulatory authorities and drug companies should alert UK doctors of the need to use the Cockcroft-Gault formula to calculate eligibility for and dosing of the new oral anticoagulants in elderly patients with AF and not rely on the MDRD-derived eGFR.